Devising and Testing a Comprehensive Physiotherapy Protocol to Improve Muscle Strength, Mass, Function and Quality of Life in Type 2 Diabetic Postmenopausal Women: A Research Protocol - Sonali Guliya; Subhasish Chatterjee (Journal of Clinical and Diagnostic Research)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic condition that can pose significant challenges for postmenopausal women, particularly in terms of their physical capabilities and overall wellbeing and they are at five times more risk of experiencing a reduction in muscle strength and mass comparison to non diabetic postmenopausal women. It poses significant health risks and requires proper management to prevent complications. Need of the study: Previous literature indicates that postmenopausal women with T2DM undergo transitions such as ageing, inadequate nutrition, sedentary lifestyle, hormonal change, insulin resistance and chronic inflammation, leading to a decrease in muscle strength and mass. Consistent physical activities, such as aerobic exercise and resistance training, have been found to improve these transitions in type 2 diabetic postmenopausal women. Therefore, there is a need to design a comprehensive physiotherapy protocol for evidence-based exercises. Aim: To design and test a comprehensive physiotherapy protocol for muscle strength, mass, function and Quality of Life (QoL) in T2DM postmenopausal women. Materials and Methods: The study will be conducted in MM Super Specialty Hospital, Ambala, Haryana, from November 2024 to June 2026. This Delphi study will be followed by a randomised controlled trial and will be divided into two phases. The first phase includes the formulation and validation of a comprehensive physiotherapy protocol. The second phase includes testing the efficacy of the protocol by conducting a randomised controlled trial on type 2 diabetic postmenopausal. Outcome measures include body composition analyser (InBody 270), back-leg-chest dynamometer, hand-held dynamometer and SarQoL questionnaire (both English and Hindi versions), which will be assessed before intervention and after six weeks of intervention. Content validation will be determined according to the Content Validity Index (CVI) values. Statistical analysis will be done by the Wilcoxon signed-rank test/paired t-test and Mann-Whitney U test/independent t-test. The significance level will be set at p-value <0.05.